A nanofiber based artificial electronic skin with high pressure sensitivity and 3D conformability. Issue 24 (2nd June 2016) - Zhong, Weibin; Liu, Qiongzhen; Wu, Yongzhi; Wang, Yuedan; Qing, Xing; Li, Mufang; Liu, Ke; Wang, Wenwen; Wang, Dong
Abstract : Pressure sensors with 3D conformability are highly desirable components for artificial electronic skin or e-textiles that can mimic natural skin, especially for application in real-time monitoring of human physiological signals. Abstract : Pressure sensors with 3D conformability are highly desirable components for artificial electronic skin or e-textiles that can mimic natural skin, especially for application in real-time monitoring of human physiological signals. Here, a nanofiber based electronic skin with ultra-high pressure sensitivity and 3D conformability is designed and built by interlocking two elastic patterned nanofibrous membranes. The patterned membrane is facilely prepared by casting conductive nanofiber ink into a silicon mould to form an array of semi-spheroid-like protuberances. The protuberances composed of intertwined elastic POE nanofibers and PPy@PVA- co -PE nanofibers afford a tunable effective elastic modulus that is capable of capturing varied strains and stresses, thereby contributing to a high sensitivity for pressure sensing. This electronic skin-like sensor demonstrates an ultra-high sensitivity (1.24 kPa −1 ) below 150 Pa with a detection limit as low as about 1.3 Pa. The pixelated sensor array and a RGB-LED light are then assembled into a circuit and show a feasibility for visual detection of spatial pressure. Furthermore, a nanofiber based proof-of-concept wireless pressure sensor with a bluetooth module as a signal transmitter is proposed and has demonstrated great promise for wireless monitoring of human physiological signals, indicating a potential for large scale wearable electronic devices or e-skin.